116k views
2 votes
Urgent please help only num 2

Urgent please help only num 2-example-1

2 Answers

2 votes

Answer: B) 4

============================================

Step-by-step explanation:

Plug in x = 3 to get

y = 3(4)^x

y = 3(4)^3

y = 3(64)

y = 192

Plug in x = 4 to get

y = 3(4)^x

y = 3(4)^4

y = 3(256)

y = 768

Now divide the two results: 768/192 = 4

This works because as x increases by 1, the y value multiplies by 4 which is the base of the exponent. So we still have "grows by a factor of 4" applying in this situation.

User LukeN
by
5.2k points
7 votes

Answer: B) 4

Step-by-step explanation:

y = 3(4)ˣ

x = 1: y = 3(4)¹

= 3 x 4

= 12

x = 2: y = 3(4)²

= 3 x 16

= 48

Growth factor from x = 1 to x = 2 is: 48 ÷ 12 = 4

x = 3: y = 3(4)³

= 3 x 64

= 192

x = 4: y = 3(4)⁴

= 3 x 256

= 768

Growth factor from x = 3 to x = 4 is: 768 ÷ 192 = 4

User BigGinDaHouse
by
5.3k points